THE SECOND WORLD WAR AND THE DRAMA OF “JALOLIDDIN MANGUBERDI” AND HIS TEXT-COMPARATIVE STUDY - Jovliyev Javlonbek (Scholar Express Journal, 2022)
This article discusses the analytical work on the text-comparative study of the manuscripts of the drama “Jaloliddin Manguberdi” by the poet and playwright Maqsud Shayxzoda.
Keywords: Maqsud; manuscript; image; laboratory